Losses and nutritional value of elephant grass silage with inclusion levels of cottonseed meal - doi: 10.4025/actascianimsci.v35i2.13736 - Pablo Teixeira Viana; Fábio Andrade Teixeira; Aureliano José Vieira Pires; Gleidson Giordano Pinto de Carvalho; Mauro Pereira de Figueiredo; Hermógenes Almeida de Santana Junior (Acta Scientiarum. Animal Sciences, 2012)
The experiment was conducted to evaluate losses and nutritive value of elephant grass silage containing increasing levels of cottonseed meal. The experimental design was completely randomized, with five treatments: 0, 7, 14, 21 and 28% inclusion of cottonseed meal, and four replications. The material was chopped and packed in PVC silos and stored for 80 days. The pH and dry matter (DM), crude protein, lignin and ether extract of the silages increased linearly with the addition of cottonseed meal, while the levels of acid detergent insoluble nitrogen, neutral detergent fiber, acid detergent fiber, cellulose and hemicellulose decreased linearly. The addition of 28% cottonseed meal reduced the in situ disappearance of DM (48h) to values lower than those of silage without additives. The concentration of ammonia nitrogen and the losses from gases and effluent were reduced. The inclusion of 28% cottonseed meal in elephant grass silage containing 18.4% DM improved the fermentation characteristics of silage more efficiently by reducing the moisture content and effluent losses, starting at the 7% level of inclusion.